In vitro anti-HIV and cytotoxic effects of pure compounds isolated from Croton macrostachyus Hochst. Ex Delile - Ermias Mergia Terefe; Faith A. Okalebo; Solomon Derese; Moses K. Langat; Eduard Mas-Claret; Nada H. Aljarba; Saad Alkahtani; Gaber El-Saber Batiha; Arabinda Ghosh; Eman A. El-Masry; Joseph Muriuki (BMC, 2022)
Abstract Croton macrostachyus is an important plant in traditional African medicine, widely utilized to treat a variety of diseases. In Kenya, HIV-infected patients use leaf and root decoctions of the plant as a cure for cough, back pain, bleeding, skin diseases, warts, pneumonia, and wounds. This study aimed to evaluate the anti-HIV activities and cytotoxic effects of extracts and chemical constituents isolated from C. macrostachyus. In our previous study we demonstrated that the hexane, CH2Cl2, ethyl acetate and methanol soluble fractions of a 1:1 v/v/ CH2Cl2/MeOH crude extracts of the leaves and stem bark of C. macrostachyus exhibited potent anti-HIV activities against HIV-1 with IC50 values ranging from 0.02-8.1 μg/mL and cytotoxicity effects against MT-4 cells ranging from IC50 = 0.58-174 μg/mL. Hence, hexane soluble extract of 1:1 v/v/ CH2Cl2/MeOH crude extract of the leaves of C. macrostachyus, that was more potent against HIV-1 at IC50 = 0.02 μg/mL was subjected to column chromatography leading to the isolation of 2-methoxy benzyl benzoate (1), lupenone (2), lupeol acetate (3), betulin (4), lupeol (5), sitosterol (6) and stigmasterol (7). Lupenone (2), lupeol acetate (3) and betulin (4) exhibited anti-HIV-1 inhibition at IC50 = 4.7 nM, 4.3 and 4.5 μg/mL respectively. The results obtained from this study support the potential of C. macrostachyus, as a source of anti-HIV constituents.